Youth Information Interaction Research in the Pandemic: Adjustments, Innovations, Implications. Issue 1 (13th October 2021) - Figueiredo, Vanessa; Meyers, Eric M.; Bilal, Dania; Rutter, Sophie; Magee, Rachel M.
Abstract: For over a year, the pandemic has forced youth to alter their routines and rely almost exclusively on technology to learn, play and connect with family and friends. Although some alterations in youth's routine seem to be temporary, some adaptations and appropriations resulting from interactions with technology will likely be forever altered. As this scenario develops, we must reflect on how these permanent changes will affect our approaches and inquiries on youth information interaction. This 90‐minute panel will convene scholars and members of the ASIS&T community interested in discussing the present and the future of digital youth research. Panelists will mediate focused conversations with participants to generate a collective account of experiences and reflections based on challenges and research plans for after the pandemic. As the implications of a global pandemic are unfolding, youth information interaction research will be critical to inform policies and programs in education and reduce digital divides.